The Longitudinal Study of Australian Children Annual Statistical Report 2010 - Maguire, B (My University, 2011)
The Longitudinal Study of Australian Children. A nationally representative longitudinal study of child development, which commenced in 2004. Data is collected from study children, their parents, carers and teachers, and through linkage with other national datasets.
Keywords: Culture and language; Childhood and child development; Culture, identity and language; Childhood and child development; Culture and identity